2005
DOI: 10.1124/jpet.104.081265
|View full text |Cite
|
Sign up to set email alerts
|

Hydrolysis of Capecitabine to 5′-Deoxy-5-fluorocytidine by Human Carboxylesterases and Inhibition by Loperamide

Abstract: Capecitabine is an oral prodrug of 5-fluorouracil that is indicated for the treatment of breast and colorectal cancers. A three-step in vivo-targeted activation process requiring carboxylesterases, cytidine deaminase, and thymidine phosphorylase converts capecitabine to 5-fluorouracil. Carboxylesterases hydrolyze capecitabine's carbamate side chain to form 5Ј-deoxy-5-fluorocytidine (5Ј-DFCR). This study examines the steady-state kinetics of recombinant human carboxylesterase isozymes carboxylesterase (CES) 1A1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
118
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 163 publications
(128 citation statements)
references
References 24 publications
9
118
1
Order By: Relevance
“…CES2 is for instance thought to be a main enzyme responsible for the conversion of irinotecan to SN-38 in humans (38), and for hydrolysis of a prodrug of gemcitabine (39). Coadministration of everolimus with ester (pro-) drugs affected by carboxylesterases, including the 5-FU anticancer prodrug capecitabine (40), should thus be assessed very carefully.…”
Section: Discussionmentioning
confidence: 99%
“…CES2 is for instance thought to be a main enzyme responsible for the conversion of irinotecan to SN-38 in humans (38), and for hydrolysis of a prodrug of gemcitabine (39). Coadministration of everolimus with ester (pro-) drugs affected by carboxylesterases, including the 5-FU anticancer prodrug capecitabine (40), should thus be assessed very carefully.…”
Section: Discussionmentioning
confidence: 99%
“…Carboxylesterases, CES1 and CES2, are responsible for the activation of 2 anticancer prodrugs, capecitabine and irinotecan (38,39). LY2334737 is cleaved only by the CES2 isozyme (11).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, it was reported that CPT-11 could be hydrolyzed by both CES1A and CES2, but the catalytic efficiency of CES2 is 60-fold higher than that of CES1A (Humerickhouse et al, 2000). In addition, the CPT-11 hydrolase activity at a substrate concentration of 2 M in HLM was potently inhibited by loperamide, which is a selective inhibitor to CES2 (Quinney et al, 2005), with an inhibitor concentration to cause 50% inhibition (IC 50 ) value of 0.46 M (data not shown). Thus, we have judged that flutamide (500 M), imidapril (100 M), and CPT-11 (2 M) could be used as the marker substrates for AADAC, CES1A1, and CES2, respectively.…”
Section: Contributions Of Aadac Ces1a1 and Ces2 To Phenacetin Hydromentioning
confidence: 99%